2019
DOI: 10.1016/j.pulmoe.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone and Nintedanib in idiopathic pulmonary fibrosis: Real-life experience in an Italian referral centre

Abstract: This study emphasizes that both antifibrotic drugs appeared to be a good therapeutic choice in terms of functional stabilization, also in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 17 publications
4
32
0
3
Order By: Relevance
“…9 Phase III clinical trials ASCEND, CAPACITY 004 and CAPACITY 006 were the first to report a significant beneficial effect of pirfenidone in reducing the decline of forced vital capacity (FVC) in patients with IPF. 10,11 Subsequent open-label extension trials and real-life multicentre studies have confirmed the efficacy of pirfenidone in reducing disease progression, [12][13][14][15][16][17] leading to a significant improvement in survival. 18,19 Safety concerns are few, including specifically gastrointestinal symptoms and photosensitivity, and can be usually resolved or mitigated through a careful management of drug assumption.…”
Section: Introductionmentioning
confidence: 97%
“…9 Phase III clinical trials ASCEND, CAPACITY 004 and CAPACITY 006 were the first to report a significant beneficial effect of pirfenidone in reducing the decline of forced vital capacity (FVC) in patients with IPF. 10,11 Subsequent open-label extension trials and real-life multicentre studies have confirmed the efficacy of pirfenidone in reducing disease progression, [12][13][14][15][16][17] leading to a significant improvement in survival. 18,19 Safety concerns are few, including specifically gastrointestinal symptoms and photosensitivity, and can be usually resolved or mitigated through a careful management of drug assumption.…”
Section: Introductionmentioning
confidence: 97%
“…Published IPF registry studies have provided insights into natural history, patient demographics, diagnostic evaluation practices, quality of life, comorbidities and health care utilization [3][4][5][6][7]. Real world experiences with anti-fibrotic use have also been reported for a single Italian center [8] and in England using administrative data [9]. Additionally, surveys have been used to explore patient and provider views about IPF treatment in Canada, France, Germany, Italy, Spain and the United Kingdom [10].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our findings, data from these studies suggest that nintedanib has a similar safety and tolerability profile in clinical practice as was observed in clinical trials. (16)(17)(18)(19)(20)(21)(22)(23) In post-marketing surveillance data from 6758 patients treated with nintedanib in the US in the year following the launch of nintedanib as a treatment for IPF, diarrhea, nausea and vomiting were the most frequently reported adverse events. (18) In an observational study of 94 patients with IPF in Greece, diarrhea was reported in 55% of patients treated with nintedanib over a follow-up period of 12 months, and 12% of patients discontinued nintedanib due to diarrhea.…”
Section: Discussionmentioning
confidence: 99%